Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2017
DOI: 10.1111/acel.12599
|View full text |Cite
|
Sign up to set email alerts
|

Endoplasmic reticulum proteostasis impairment in aging

Abstract: SummaryPerturbed neuronal proteostasis is a salient feature shared by both aging and protein misfolding disorders. The proteostasis network controls the health of the proteome by integrating pathways involved in protein synthesis, folding, trafficking, secretion, and their degradation. A reduction in the buffering capacity of the proteostasis network during aging may increase the risk to undergo neurodegeneration by enhancing the accumulation of misfolded proteins. As almost one‐third of the proteome is synthe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
114
0
4

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 172 publications
(129 citation statements)
references
References 123 publications
(146 reference statements)
2
114
0
4
Order By: Relevance
“…This remarkable effect relies on translation-dependent remodeling of neuronal synapses (20). eIF2 phosphorylation correlates with diverse neurodegenerative diseases and cancers, as well as normal aging (21)(22)(23)(24). Additionally, a number of mutations that impair eIF2B activity lead to a neurodegenerative disorder of childhood known as vanishing white matter disease (VWMD) that is marked by cerebellar ataxia, spasticity, hypersensitivity to head trauma and infection, coma and premature death (25).…”
Section: Main Textmentioning
confidence: 99%
“…This remarkable effect relies on translation-dependent remodeling of neuronal synapses (20). eIF2 phosphorylation correlates with diverse neurodegenerative diseases and cancers, as well as normal aging (21)(22)(23)(24). Additionally, a number of mutations that impair eIF2B activity lead to a neurodegenerative disorder of childhood known as vanishing white matter disease (VWMD) that is marked by cerebellar ataxia, spasticity, hypersensitivity to head trauma and infection, coma and premature death (25).…”
Section: Main Textmentioning
confidence: 99%
“…Accumulation of intracellular aggregates composed by misfolded proteins during aging deteriorates cellular function. 24) Consistently, we previously found that muscular taurine depletion activates unfolded protein response (UPR) signal pathway, 22) which may be resulted from impairment of protein homeostasis by taurine loss. Therefore, we tested whether endoplasmic reticulum (ER) stress is associated with an induction in GDF15.…”
Section: Induction In Gdf15 In Aged Tautko Musclementioning
confidence: 73%
“…We have reported that Wrn Dhel/Dhel mice exhibit a 20% increase in ROS levels in the liver ER enriched fractions compared with age-matched WT mice (29). The ER is the main site for the synthesis and folding of around one-third of the total proteome of a cell (66). Proper folding of nascent protein in the ER requires an oxidant environment.…”
Section: Mouse Modelmentioning
confidence: 99%